The European Commission's report on Turkey: An intelligent guide - Heinz Kramer; Hanna-Lena Krauß (Stiftung Wissenschaft und Politik (SWP), 2004)
On 17 December, the European Council will decide whether or not to open accession negotiations with Turkey. Its decision will be based on the comprehensive Turkey report presented by the Commission on 6 October which serves as an intelligent guide for drawing up the negotiating mandate as well as preparing for the actual negotiations themselves. It explains why the negotiations with Turkey will be conducted in a different way, indeed why owing to both parties' interest in a successful outcome they have to be organised differently than the talks concluded with countries in past waves of enlargement. The European Council should take full account of the Turkey report and the recommendations contained therein when making its decision. (SWP Comments / SWP)
Keywords: 320